Comfort, ocular dryness, and equilibrium water content changes of daily disposable contact lenses - Insua, Eduardo Pereira (2018)
Objectives: The objective of this investigation was to evaluate the level of comfort and ocular dryness during wear with six daily disposable contact lenses (DDCL) and also determine the changes in contact lens equilibrium water content (EWC) resulting from their wear. Methods: In this contralateral open trial, 27 subjects were randomly fitted with six DDCL (stenfilcon A, delefilcon A, nelfilcon A, narafilcon A, nesofilcon A, and omafilcon A). The evaluation of comfort and ocular dryness sensation was recorded by the participants at two moments of the day (11 AM and 5 PM) over a period of 10 days of contact lens wear. The assessment was made with the aid of visual analogue scales (0–10). The refractive index of 54 contact lenses was accessed by a single operator using a digital automated refractometer (CLR 12-70; Index Instruments). The EWC of the lenses was estimated based on its refractive index values. Results: Comfort ratings were slightly higher for delefilcon A (9.5660.67, P¼0.01) and narafilcon A (9.4060.93, P¼0.01) and these lenses wearers also reported less ocular dryness. The results revealed a pronounced water content reduction for omafilcon A (P¼0.002), narafilcon A (P¼0.008), and nesofilcon A (P¼0.003). Conclusion: Although changes in subjective responses and EWC were distinct among the materials analyzed, all the contact lenses performed well during the 10 days of wear.